Exercise programs improve mobility and balance in people with Parkinson's disease - Gobbi, Lilian T.B. [UNESP]; Oliveira-Ferreira, Maria D.T. [UNESP]; Caetano, M. Joana D. [UNESP]; Lirani-Silva, Ellen [UNESP]; Barbieri, Fabio A. [UNESP]; Stella, Florindo [UNESP]; Gobbi, Sebastião [UNESP] (Elsevier, 2009)
Compromised balance and loss of mobility are among the major consequences of Parkinson's disease (PD). The literature documents numerous effective interventions for improving balance and mobility. The purpose of this study was to verify the effectiveness of two exercise programs on balance and mobility in people with idiopathic PD. Thirty-four participants, with idiopathic PD that ranged from Stage I to Stage III on the Hoehn & Yahr (H&Y) scale, were assigned to two groups. Group 1 (n = 21; 67±9 years old) was engaged in an intensive exercise program (aerobic capacity, flexibility, strength, motor coordination and balance) for 6 months: 72 sessions, 3 times a week, 60 minutes per session; while Group 2 (n = 13; 69±8 years old) participated in an adaptive program (flexibility, strength, motor coordination and balance) for 6 months: 24 sessions, once a week, 60 minutes per session. Balance and basic functional mobility were assessed in pre- and post-tests by means of the Berg Balance Scale and the Timed Up and Go Test. Before and after the interventions, groups were similar in clinical conditions (H&Y, UPDRS, and Mini-Mental). A MANOVA 2 (programs) by 2 (moments) revealed that both groups were affected by the exercise intervention. Univariate analyses showed that participants improved their mobility and balance from pre- to post-test. There were no differences between groups in either mobility or balance results. Both the intensive and adaptive exercise programs improved balance and mobility in patients with PD. © 2009 Elsevier Ltd. All rights reserved.
Keywords: Balance; Exercise; Mobility; Parkinson's disease; antiparkinson agent; aerobic capacity; aged; body equilibrium; clinical article; controlled study; female; human; intermethod comparison; kinesiotherapy; male; mini mental state examination; motor coordination; muscle strength; Parkinson disease; patient mobility; priority journal; therapy effect; Unified Parkinson Disease Rating Scale; Aged; Disability Evaluation; Exercise Therapy; Female; Gait Disorders, Neurologic; Humans; Male; Middle Aged; Multivariate Analysis; Parkinson Disease; Postural Balance; Severity of Illness Index; Time Factors; Walking